Proposed upgrading work for existing public toilet at Coliseum Car Park Plaza, Jalan Tuanku Abdul Rahman, Kuala Lumpur for MESSRS Dewan Bandaraya Kuala Lumpur (DBKL) / Hasni Mohd Noor - Mohd Noor, Hasni (Faculty of Architecture, Planning and Surveying, 2005)
This final project report had been carried out to provide a basic reference that will give a guide line to professional and government agencies in designing a good public toilet that is suitable for Malaysian. This final project report will help to create an ideal toilet that is really conducive and can be appreciated by our local society. It is important that we should set a basic requirement based on our society’s needs, culture, climate and other important factors. This is because today toilets are merely designed based on the standard set by different countries in the West that does not specifically design to suit our culture, habits and social behaviors which in general are very much different from them. The reason why this final project report is so important is obvious. There seem too many complaints on the standard of the public toilets in Malaysia. Why is it so bad? Well, the main reason behind it is basically our own attitude, which can be avoided by understanding it. For example, it is found out the sitting WC tends to spoil easily than the squatting type. Most of it spoils because some people prefer squatting on it. This happened because squatting is the only way Malaysian perform their ‘businesses’ inside the toilet. Other than that, they also squat simply because the WC is so dirty for them to sit on or to avoid getting infected by any venereal diseases. If this aspect had been considered, all those problems will not have occurred. Besides that, there are so many different aspects need to be studied, such as types of facilities to be provided, innovative ways of designing toilets, improving the hygienic factor and etc. So through this final project report, it is hope that all of the aspects can be carefully looked into and all those problems could be resolved.